Ground state of CH2+: experimental aspects and theoretical implications - Baer, A.; Grieser, Manfred; Knoll, L.; Levin, J.; Repnow, Roland; Schwalm, Dirk; Vager, Z.; Wester, Roland (Physical review. A, Atomic, molecular, and optical physics, 1999)
Hot CH+2 molecular ion ensembles were prepared, accelerated, and stored for radiative cooling to room temperature. The structure of the species was measured by the Coulomb explosion imaging method at different stages of cooling. The bending angle distributions were extracted and compared with recent theories as well as a previous Coulomb explosion imaging measurement. The comparison reveals an apparent large nonadiabatic contribution to the low-lying CH+2 wave functions.
Im Titel ist "+" hochgestellt und "2" tiefgestellt
Gesehen am 30.11.2020